Key knowledge to support phonological awareness and phonics instruction (New Jersey: Wiley Company, 2022)
What do teachers need to know about phonological awareness and phonics instruction to support beginning teachers? Understanding these concepts and enacting effective teaching practices require considerable specialized knowledge.